2017
DOI: 10.1007/82_2017_68
|View full text |Cite
|
Sign up to set email alerts
|

Mining the Complex Family of Protein Tyrosine Phosphatases for Checkpoint Regulators in Immunity

Abstract: The family of protein tyrosine phosphatases (PTPs) includes 107 genes in humans that are diverse in their structures and expression profiles. The majority are present in immune cells and play various roles in either inhibiting or promoting the duration and amplitude of signaling cascades. Several PTPs, including TC-PTP (PTPN2) and SHP-1 (PTPN6), have been recognized as being crucial for maintaining proper immune response and self-tolerance, and have gained recognition as true immune system checkpoint modulator… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 106 publications
0
13
0
Order By: Relevance
“…PTPN6, a non-receptor protein tyrosine phosphatase also known as SHP-1, is an important protein that regulates basic cellular processes and acts as a checkpoint regulator to maintain appropriate immune responses and self-tolerance 39,40 . In addition, PTPN6 has been reported to control cell proliferation and determine the therapeutic potential of somatostatin in pancreatic cancer 41 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PTPN6, a non-receptor protein tyrosine phosphatase also known as SHP-1, is an important protein that regulates basic cellular processes and acts as a checkpoint regulator to maintain appropriate immune responses and self-tolerance 39,40 . In addition, PTPN6 has been reported to control cell proliferation and determine the therapeutic potential of somatostatin in pancreatic cancer 41 .…”
Section: Discussionmentioning
confidence: 99%
“…Here, we demonstrated that low TLR1 and ADA2 expression play vital roles in pancreatic cancer immunity and can both mediate immune cell infiltration to affect tumor immune status. PTPN6, a non-receptor protein tyrosine phosphatase also known as SHP-1, is an important protein that regulates basic cellular processes and acts as a checkpoint regulator to maintain appropriate immune responses and self-tolerance [ 39 , 40 ]. In addition, PTPN6 has been reported to control cell proliferation and determine the therapeutic potential of somatostatin in pancreatic cancer [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…The GAP activity of Rasal1 differs from the mode of action of other established negative regulators, such as the SHP-1/2 phosphatases and the E3 ubiquitin ligases. SHP-1/2 dephosphorylate substrates 62 , and E3 ligases such as Cbl-b, Itch and Grail regulate the ubiquitin pathway 25 . Perhaps the most similar mediator is the CAPRI (Ca 2+ promoted Ras inactivator), which is also a Ca 2+ -dependent GAP that switches off the Ras-MAPK pathway following stimuli that elevate intracellular Ca 2+ 40 .…”
Section: Discussionmentioning
confidence: 99%
“…It is likely that tyrosine phosphatases have emerged alongside their kinase counterparts and have allowed the eukaryotic to set up new cell–cell signaling pathways [ 24 ]. It is therefore not surprising that deregulations of the expression or catalytic activity of these phosphatases can lead to disruption of immunity [ 32 , 33 ], organ dysfunction such as heart failure [ 34 ], or diseases such as cancer [ 35 , 36 , 37 ]. It is thus astonishing to observe that Apicomplexa have found ways to minimize the use of tyrosine phosphorylation.…”
Section: Apicomplexan Serine/threonine and Tyrosine Phosphatomementioning
confidence: 99%